Validitas multimedia interaktif berbantuan i-spring suite 8 berdasarkan edupark fisika untuk siswa sma kelas X - Viviandri Viviandri; Hamdi Hamdi; Akmam Akmam; Fatni Mufit (PILLAR OF PHYSICS EDUCATION, 2020)
This research aims to find out the validity level of interactive multimedia. This research is a type of development research using the plomp model . Data source of research this is a team validator includes three physics major of FMIPA UNP's lecturers. teacher of physics SMA Negeri 2 Lubuk Basung, as well as students SMA Negeri 2 Lubuk Basung and some student at High School in the city of Padang and cities Pariaman . Instruments research were used in the study is that the instrument Student observation questionnaire , teacher interview instrument , and validation instrument . Instruments The study then validated first advance by experts . Data analysis technique in this research is descriptive statistical analysis technique . Based on data analysis two conclusions can be drawn . First , multimedia interactive  i-spring suite 8 based edupark physics has a characteristic that is composed of a title , profile , user usage , material physics that is associated with edupark physics mifan waterpark Padang Panjang , evaluation , and reference . Secondly , validation of multimedia interactive aided i-spring suite 8 based edupark physics has a value of the validity of the strong . The validity characteristics of this product are in terms of material substance , learning design , appearance ( communication , visual), and software utilization